Implementation of a Smart Lock with Face Recognition Module and Vibration Sensor as an Automatic Door Security System: Telekomunikasi Militer - Atnanta Masa Samodera; Imam Ashar; Riza Hasbi (Jurnal Telkommil, 2026)
As Internet of Things (IoT) technology develops, the demand for more sophisticated and automated security systems is also increasing. This research aims to design and implement a Smart Lock system based on facial recognition integrated with a vibration sensor to enhance automatic door security. The system uses an ESP32-CAM as the main microcontroller, a Solenoid Door Lock as the locking actuator, and an SW-420 vibration sensor to detect physical disturbances. The method used in this study is system engineering experimentation, starting from hardware design, module programming, and functional system testing. Data was collected to measure the accuracy of facial recognition, the sensitivity of the vibration sensor, and the response of the automatic door lock actuator. Test results show that the system can detect authorized user faces with up to 90% accuracy at an optimal distance of 50–80 cm. The vibration sensor also quickly responds to disturbances, sending signals to the system to trigger alarms or notifications. The system has been tested in several simulation scenarios and produced stable results.